Leadership and organizational culture in small companies - Cantermi, Bruno de Amorim; Antonieta Lizote, Suzete (Revista de Administração da UFSM, 2022)
Purpose: To evaluate the relationship between organizational culture and the leadership performed by man-agers of micro and small companies. Methodology: The research has a quantitative and descriptive approach. Self-administered questionnaires applied to managers were used as a data collection instrument, resulting in a sample of 82 respondents. For data analysis, descriptive and correlational techniques were used. Results: The results showed that the transactional leadership style was the most perceived in managers and the type of current predominant culture was the clan culture. When testing the conjectured hypotheses, dif-ferent relationships between organizational culture and its dimensions were found with leadership styles. Clan culture showed correlation with all dimensions. Practical implications: In practical terms, the research will be able to contribute to the micro and small compa-nies of intimate fashion and their managers, presenting new perspectives of management and development of competitive strategies, from the understanding of the leadership styles of the managers and the organizational culture of the company. company. Originality: Based on the research found, it appears that both organizational culture and leadership have been component variables of some mediation and moderation models that relate personal and organizational var-iables, but publications have not been identified in the literature that directly investigate the culture and its relationship with leadership styles in small textile companies.